Brits and British Muslims and their perceptions of cultured meat: How big is their willingness to purchase?. Issue 3 (18th June 2022) - Boereboom, Anouk; Sheikh, Mustapha; Islam, Tajul; Achirimbi, Elma; Vriesekoop, Frank
Abstract: Consumer preferences regarding food in general, livestock meat and cultured meat among Muslim populations remains largely unknown, especially in a United Kingdom context. This is a significant gap in our understanding since foods that meet halal requirements have a major economical share of both the British and the global food market. The aim of this study is threefold: (1) gain insight into the perceptions of the broader British community and the Muslim demographic within it regarding food choice determinants, livestock meat, and cultured meat; (2) investigating similarities and differences within and between the two groups; and (3) model the willingness to purchase (WTPu) cultured meat for both populations. The British Muslim and the British non‐Muslim population are very similar in their considerations about food in general, livestock meat and cultured meat. With regard to the willingness to purchase cultured meat, further product development and marketing strategies should focus on the same factor for both populations: the healthiness, safety, and nutritional characteristics of cultured meat. Abstract :